The Mediating Effect of Brand Commitment on The Relationship Between Brand Credibility and Brand Loyalty: Case Study of Aqua Bottled Drinking Water in Indonesia - Nilasari, Irma; Astuti Pratminingsih, Sri; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Aqua is a market leader in the bottled drinking water industry in Indonesia. However, although AQUA holds the position of number one in the top brand index (TBI) in Indonesia, data from www.topbrand-award.com shows that from 2016 until 2019, the TBI rank of AQUA is decreasing. The present study is aimed at exploring brand loyalty with respect to brand credibility and brand commitment. The result shows that brand credibility and brand commitment positively influence brand loyalty. Brand commitment is proven to be a mediator in the relationship between brand credibility and brand loyalty. The present study proposes some practical implications.